2020
DOI: 10.1093/ejcts/ezaa007
|View full text |Cite
|
Sign up to set email alerts
|

Utility of double arterial cannulation for surgical repair of acute type A dissection

Abstract: OBJECTIVES Outcomes of planned and unplanned (rescue) double arterial cannulation (DAC) in surgery for acute type A aortic dissection were investigated retrospectively. METHODS The study involved 805 patients who were divided into 4 groups according to the cannulation strategy: single cannulation of the femoral artery (n = 338), axillary artery (n = 256), left ventricular apex (n = 52) or ascending aorta (n = 5) (total, n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…However, we didn’t find any difference on in-hospital mortality and follow-up survival between DAC and RAC group in our 431 patients’ study. Our results were similar to the study from Kusadokoro et al [ 22 ], they found that DAC had acceptable early and long-term follow-up results for both planned and unplanned (rescue) ATAAD surgery.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we didn’t find any difference on in-hospital mortality and follow-up survival between DAC and RAC group in our 431 patients’ study. Our results were similar to the study from Kusadokoro et al [ 22 ], they found that DAC had acceptable early and long-term follow-up results for both planned and unplanned (rescue) ATAAD surgery.…”
Section: Discussionsupporting
confidence: 91%
“…It arouses curiosity whether cannulation strategies differ in terms of perioperative parameters in ATAAD patients. Kusadokoro et al [ 22 ] reported that they preferred DAC in patients with true lumen stenosis and perioperative leg malperfusion. However, even with propensity score matching, the trend that DAC group were younger and with lower incidence of perioperative shock was still seen.…”
Section: Discussionmentioning
confidence: 99%
“…Acute dissection was referred to onset within 14 days, and emergency surgery was defined as operation performed within 24 h after hospital arrival. Retrograde perfusion was referred to performing cardiopulmonary bypass (CPB) with cannulation site of the femoral artery, including double arterial cannulation ( 8 ). We collated clinical data retrospectively from laboratory reports, radiological examination reports, and medical charts, follow-up data were obtained by telephone interview or clinic visits.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies have confirmed that DAC can provide satisfactory cerebral and distal organ protection and avoid deep hypothermia-related side effects (56,57). The greatest advantage of DAC is that the RAAC can make up for the femoral artery-induced false cavity perfusion and that FAC can compensate for the insufficient flow of the RAAC.…”
Section: Double Arterial Cannulation (Dac)mentioning
confidence: 98%
“…This is because it can reduce postoperative complications associated with poor perfusion. Thus, DAC is effective for both the prevention and management of intraoperative malperfusion (56). In order to better understand, we had made some summaries in Table 1.…”
Section: Double Arterial Cannulation (Dac)mentioning
confidence: 99%